2021
DOI: 10.1158/1055-9965.epi-21-0507
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary and Inflammatory Bowel Disease-Related Early Onset Colorectal Cancer Have Unique Characteristics and Clinical Course Compared with Sporadic Disease

Abstract: Background: Early onset colorectal cancer (EoCRC), diagnosed in those <50 years old, is increasing in incidence. We sought to differentiate characteristics and outcomes of EoCRC in patients with sporadic disease or preexisting conditions. Methods: We evaluated 2,135 patients with EoCRC in a population-based cohort from the Canadian province of British Columbia. Patients were identified on the basis of presence of hered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Currently, anoikis resistance correlates with a variety of characteristic tumor processes. Du et al revealed biological interactions between critical elements of anoikis resistance and angiogenesis, which promoted peritoneal metastasis in gastric cancer and showed promise as a potential prognostic biomarker and therapeutic target ( Arif et al, 2021 ). Bárbara et al demonstrated that metabolic remodeling and antioxidant processes in breast cancer can promote anoikis resistance, thus promoting the survival of breast cancer cells at circulating and metastatic sites ( Sousa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, anoikis resistance correlates with a variety of characteristic tumor processes. Du et al revealed biological interactions between critical elements of anoikis resistance and angiogenesis, which promoted peritoneal metastasis in gastric cancer and showed promise as a potential prognostic biomarker and therapeutic target ( Arif et al, 2021 ). Bárbara et al demonstrated that metabolic remodeling and antioxidant processes in breast cancer can promote anoikis resistance, thus promoting the survival of breast cancer cells at circulating and metastatic sites ( Sousa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study that tracked individuals diagnosed with early onset colorectal cancer found that patients with a history of inflammatory bowel diseases exhibited higher occurrences of metastatic disease, a reduced degree of histological differentiation, and increased presence of lymphovascular and perineural invasion, in comparison to those with sporadic cancer [ 36 ]. Additionally, these patients experienced lower rates of survival, with statistical significance at a p -value of less than 0.0001 [ 36 ]. The prognosis did not differ between ulcerative colitis and Crohn’s disease, but it was worse for individuals with undifferentiated inflammatory bowel disease ( p = 0.049) [ 36 ].…”
Section: Risk Factors For Colorectal Cancersmentioning
confidence: 99%
“…These authors hypothesized that the chronic inflammation associated with inflammatory bowel diseases could result in a specific genetic profile, which could explain the poor prognosis of this malignant condition [36]. They also noted a higher prevalence of mucinous and signet ring histology (negative prognostic factors) in the inflammatory bowel disease population, as well as higher rates of positive surgical margins [36].…”
Section: Risk Factors For Colorectal Cancersmentioning
confidence: 99%